Adaptive Climate Actions (Global Journals of Research in Engineering, 2023)
Adaptive Climate Actions are activities aimed at ensuring the safety of the population and reducing the damage caused by climate change Catastrophic phenomena that occur during the global transformation of climatic conditions are diverse Therefore the development of various Adaptive Climate Actions is required The most important is to minimize the negative effects of catastrophic events such as floods rising ocean levels abnormal floods droughts forest fires reduced crop yields the spread of undesirable organisms and ecological frustrations Some dangerous phenomena and processes develop simultaneously and are interdependent In these cases it is advisable to develop integrated programs combining several different activities
Keywords: adaptive climate actions; ocean level rise; abnormal droughts and floods; forest fires; reduced crop